Effect of increased quadriceps tensile stiffness on peak anterior cruciate ligament strain during a simulated pivot landing. Issue 3 (2nd December 2013) - Lipps, David B.; Oh, Youkeun K.; Ashton‐Miller, James A.; Wojtys, Edward M.
ABSTRACT ACL injury prevention programs often involve strengthening the knee muscles. We posit that an unrecognized benefit of such training is the associated increase in the tensile stiffness of the hypertrophied muscle. We tested the hypothesis that an increased quadriceps tensile stiffness would reduce peak anteromedial bundle (AM‐)ACL relative strain in female knees. Twelve female cadaver knees were subjected to compound impulsive two‐times body weight loads in compression, flexion, and internal tibial torque beginning at 15° flexion. Knees were equipped with modifiable custom springs to represent the nonlinear rapid stretch behavior of a normal and increased stiffness female quadriceps (i.e., 33% greater stiffness). Peak AM‐ACL relative strain was measured using an in situ transducer while muscle forces and tibiofemoral kinematics and kinetics were recorded. A 3D ADAMS™ dynamic biomechanical knee model was used in silico to interpret the experimental results which were analyzed using a repeated‐measures Wilcoxon test. Female knees exhibited a 16% reduction in peak AM‐ACL relative strain and 21% reduction in change in flexion when quadriceps tensile stiffness was increased by 33% (mean (SD) difference: 0.97% (0.65%), p = 0.003). We conclude that increased quadriceps tensile stiffness reduces peak ACL strain during a controlled study simulating a pivot landing. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:423–430, 2014.